Land Banking Establishment as the First Step Acceleration for Post COVID-19 Pandemic Investment - Vincensia Esti Purnama Sari; Serlly Waileruny; Graceyana Jennifer (Faculty of Law, Universitas Pekalongan, 2022)
The collapse of the country's economy as a result of the COVID-19 pandemic is necessary to be resurrected, one of which is through investment, including investment inland. Thus, through the Law of Republic Indonesia No. 11 of 2020 on Job Creation and Government Regulation No. 64 2021 on Land Banking, the government has defined the formation of a body of Land Banking that has been authorized specifically to manage land. Does this post to highlight two issues: 1) the urgency of the bank's establishment in response to the question of the land itself in Indonesia's investment activities? 2) the role of the bank bodies as the first step acceleration of the national economy post-covid-19 pandemic? The research method used was the juridic-normative law research method, which used secondary data and was acquired through literature studies. According to the authors, there are at least 3 problems in the land: a) license and bureaucratic deliberations; b) the lengthy process of land acquisition; and c) high cost. However, the presence of ground bank agencies as the land keeper, land warranty, land valuer, land distributor, land manager, can help to accelerate the investment.Keywords: Land Banking, Investment Acceleration, COVID-19 Pandemic